PROBLEMS OF CHILDHOOD AND EDUCATION IN CHARLES DICKENS’ WORKS - Tuychiboeva Shakhlo Zayniddin qizi, Elvina Reshatovna Kenjali (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Charles Dickens took children as example of nineteenth century with poverty and uneducated lifestyle. Through his novels, he showed emotions of children when they faced trouble as an orphan. The main novels of him were “ Oliver Twist’ and “David Copperfield” that emphasized the themes of child labor and social injustice. Drawing from personal experience, Dickens advocated for social reform and highlighted the transformative power of education in uplifting disadvantaged youth.